DETERMINING THE BURNOUT LEVEL OF THE PERSONNEL IN THE 25th WINTER UNIVERSIADE COORDINATION CENTER - Emre Belli; Dursun Katkat1; M. Alparslan Kurudirek (Pamukkale University, 2012)
The aim of this research is to assess the burnout levels of the personnel in 25 th Winter Universiade, Erzurum 2011 Coordination Center and to comprehend whether there is any reaction to some demographic factors or not. In this research, Maslach Burnout Inventory (MTE) developed by Maslach and Jackson (1981) and translated into Turkish by Ergin (1922) was applied on 79 women and 144 men, 223 in total working for the coordination to acquire data about the burnout level. During the statistical evaluation of the acquired data, frequency analysis, descriptive statistics, independent Group t-test and single sided variance analysis (Anova) were applied. There has been no great difference among the burnout levels concerning gender, status, education and marital status.(p>0,05)